PROBLEMS OF ISLAMIC HOME FINANCING IN INDONESIA: A TAHWIDI STRING RELATION (TSR) EXPOSITION - Bambang Wijananto; Yuswar Zainul Basri; Akhmad Affandi Mahfudz; Akhmad Suraji (Tazkia Islamic Finance and Business Review, 2020)
This study intends to explore and analyze Home Islamic financing problems in Indonesia by using the Tawhidi String Relations (TSR) approach, a methodology that uses the Quran and Sunnah as ontology in each solution to variables in achieving wellbeing. TSR has advantages over the concepts of Interaction, Integration and Evolution (IIE). The variables of this study are Human Resources, Internal Controls and Regulators, who represent internal and external interests. This study found that the IHF problems must be overcome by the concept of changing religious values into economic activities referring to the Quran and Hadith which are presented practically in the real world as a universally applicable basis in achieving Maqasid Sharia.